Misinformation on cardiovascular disease spreads through social networks: a scoping review protocol - Buna Bhandari; Jessica Hanae Zafra-Tanaka; Maria M Infante-Garcia; Juan P Gonzalez-Rivas; Pranab Mahapatra; Marina Njelekela; Sudha Ramalingam (BMJ Open)
Introduction Misinformation about cardiovascular health has the potential to negatively impact public health outcomes. Understanding the nature and spread of such misinformation is crucial for developing effective interventions to mitigate this potential risk. However, despite the critical importance of this issue, there is a gap in comprehensive reviews mapping the existing literature on cardiovascular health misinformation. This scoping review aims to map the existing literature on cardiovascular health misinformation, identifying its spread, prevalence, impact and strategies for correction across diverse populations and settings.Methods This review will follow the Joanna Briggs Institute guidelines for conducting a scoping review. A comprehensive search will be conducted across multiple databases, including MEDLINE, EMBASE, SCOPUS and Web of Science, along with grey literature sources. The last date of search was January 2025. The review will include studies without date that involve individuals affected by cardiovascular disease (CVD) misinformation, examine the spread, prevalence, impact or correction of misinformation related to cardiovascular health, and capture various cultural, geographic or setting-specific factors. The exclusion criteria include studies that do not directly address misinformation related to CVD. All identified records will be imported into Covidence systematic review software. Two reviewers will independently screen titles and abstracts, followed by full-text reviews of potentially relevant studies. Discrepancies will be resolved through discussion or by consulting a third reviewer. Data extraction will be conducted by two reviewers using a pre-piloted tool, and a descriptive presentation of the findings will be done. Both inductive and deductive content analysis methods will be employed for objectives related to the impact and strategies to combat misinformation.Ethics and dissemination Given that the study involves synthesising data from existing published literature, ethical approval is not required. The findings will be disseminated through international conference presentations, published in a peer-reviewed journal and shared with public health organisations and policymakers.